Shedding the cobra effect: problematising thematic emergence, triangulation, saturation and member checking. Issue 1 (January 2017) - Varpio, Lara; Ajjawi, Rola; Monrouxe, Lynn V; O'Brien, Bridget C; Rees, Charlotte E
Abstract : Discuss ideas arising from the article atwww.mededuc.com discuss. Abstract : Context: Qualitative research is widely accepted as a legitimate approach to inquiry in health professions education (HPE). To secure this status, qualitative researchers have developed a variety of strategies (e.g. reliance on post‐positivist qualitative methodologies, use of different rhetorical techniques, etc.) to facilitate the acceptance of their research methodologies and methods by the HPE community. Although these strategies have supported the acceptance of qualitative research in HPE, they have also brought about some unintended consequences. One of these consequences is that some HPE scholars have begun to use terms in qualitative publications without critically reflecting on: (i) their ontological and epistemological roots; (ii) their definitions, or (iii) their implications. Objectives: In this paper, we share our critical reflections on four qualitative terms popularly used in the HPE literature: thematic emergence; triangulation; saturation, and member checking. Methods: We discuss the methodological origins of these terms and the applications supported by these origins. We reflect critically on how these four terms became expected of qualitative research in HPE, and we reconsider their meanings and use by drawing on the broader qualitative methodology literature. Conclusions: Through this examination, we hope to encourage qualitative scholars in HPE to avoid using qualitative terms uncritically and non‐reflexively.